The Current trends of Corporate Social and Environmental Reporting (CSER) in Bangladesh - Hossain, Mohammad; Rowe, Anna; Quaddus, Mohammed (A-CSEAR, 2012)
Purpose – The purpose of this paper is to investigate the current trends of corporate social and environmental reporting of the top 20 companies on the Dhaka Stock Exchange (DSE), Bangladesh.Design/methodology and approach- A qualitative research approach has chosen in this study and the authors utilized the content analysis of annual reports (2010-2011) and other publicly available documentary evidence according to six major criteria with 66 indicators. The top companies have been selected based on market capitalisation.Findings- The finding of this research shows that organizations in Bangladesh disclose more on community and development which is 69% followed by governance code and policies which is 67%. The study also finds that organizations are paying limited attention to workplace/HR disclosure and environment that is 38% and 28% respectively. The banking and financial companies disclose more on social and environmental issues with compare to other sector organizations because of institutional pressure from central bank.Research implications- The aim and value added contribution of this paper is the potential to raise awareness among company boards and senior managers concerning reporting and communicating of social, environmental and governance issues.Original Value- The paper provides useful information about the social and environmental disclosures by top listed companies in Dhaka Stock Exchange (DSE), Bangladesh. This paper uses most recent data for content analysis to examine the social and environmental disclosures in a developing country where corporate governance and voluntary disclosure still at initial stage.